Analysis and visualization of airport network to strengthen the economy - P, Saleena.; Swetha, P. K.; Radha, D. (International Journal of Engineering and Technology, 2018)
The worldâ€™s eminent airports are directly or indirectly connected to many other airports. Every airport is considered as a node and the route can be considered as edge connecting them. The work analyzes the USA airport network using different centrality measures of social network analysis. The centrality measures calculated on airport network help in identiï¬cation of certain characteristics of the airports. Some of the characteristics are like the busiest airport and the airports which inï¬‚uence trade, alternate path, fastest route, nearest airports, etc. The characteristics helps to find the designated airports meant for improving the economy. The results of this paper say about the prominent communication and connections among the airports in the U.S.A. The tools used for the analysis are UCINET 6 and NetDraw.Â